Regulatory role of natural killer T cells in diabetes - Tard, Celine (Biomed J, 2015)
Type 1 and type 2 diabetes are growing public health problems. Despite having different pathophysiologies, both diseases are associated with defects in immune regulation. Invariant natural killer T (iNKT) cells are innate-like T cells that recognize glycolipids presented by CD1d. These cells not only play a key role in the defense against pathogens, but also exert potent immunoregulatory functions. The regulatory role of iNKT cells in the prevention of type 1 diabetes has been demonstrated in murine models and analyzed in diabetic patients. The decreased frequency of iNKT cells in non-obese diabetic mice initially suggested the regulatory role of this cell subset. Increasing the frequency or the activation of iNKT cells with agonists protects non-obese diabetic mice from the development of diabetes. Several mechanisms mediate iNKT regulatory functions. They can rapidly produce immunoregulatory cytokines, interleukin (IL)-4 and IL-10. They induce tolerogenic dendritic cells, thereby inducing the anergy of autoreactive anti-islet T cells and increasing the frequency of T regulatory cells (Treg cells). Synthetic agonists are able to activate iNKT cells and represent potential therapeutic treatment in order to prevent type 1 diabetes. Growing evidence points to a role of immune system in glucose intolerance and type 2 diabetes. iNKT cells are resident cells of adipose tissue and their local and systemic frequencies are reduced in obese patients, suggesting their involvement in local and systemic inflammation during obesity. With the discovery of potential continuity between type 1 and type 2 diabetes in some patients, the role of iNKT cells in these diseases deserves further investigation.